Creative Research Communication Theory and Practice - Wilkinson, Clare and Weitkamp, Emma (Manchester University of Press, 2016)
This book provides a theoretically grounded introduction to new and emerging approaches to public engagement and research communication. -
Include Index and References
Keywords: Universities and colleges--Public relations -- Communication in higher education -- Social sciences--Research--Methodology